Application of Extended Adomian Decomposition Method and Extended Variational Iteration Method to Hirota-Satsuma Coupled KdV Equation - İnç, Mustafa; Gencoglu, M. Tuncay; Akgul, Ali (Amer Scientific Publishers, 2017)
We acquire series solutions of Hirota-Satsuma coupled KdV (HSCKdV) equation with initial condition by using extended adomian decomposition method (EADM) and extended variational iteration method (EVIM). We compare these solutions with the some solutions that are exist in the literature. Obtained tables and figures show that EADM and EVIM give more accurate results than some methods in the literature. Furthermore, approximate solution that obtained by the convergence parameter of these methods is closer to the exact solution for big and small values of the time.
Keywords: EADM; EVIM; HSCKdV Equation